Perception of health sciences professors about adaptation to remote education - Garcia , Fabiane Weber (2022)
Faced with the pandemic scenario, higher education institutions needed to reinvent teaching-learning methods, adopting the remote modality. In this setting, a qualitative study was carried out using the exploratory-descriptive method, with 16 professors from an educational institution in Curitiba – PR, who work in the health area and adopted the remote teaching modality during the pandemic period. Content Analysis proposed by Bardin was used to extract information, aiming to describe the perception of professors regarding the adaptation to remote teaching and the challenges arising from the pandemic. As a result, the following categories were listed: I) Professor's perception regarding adaptation to remote teaching: II) Professor's perception regarding the student in the remote teaching modality. It is concluded that the professors perceived the moment as challenging and of resilience, eliciting the need for new learning, in a process that involved the institution, its managers, professors, and students.